Level of mastery in using verbs among form four full boarding schools students - Isa, Annuar Khisham; Hamzah, Zaitul Azma Zainon; Sha’ri, Sharil Nizam (UPSI Press, 2021)
A branch of general linguistics that describes the rules or laws of a language is grammar. The combination of words to produce sounds and phrases is of two forms, namely morphology and syntax. Grammar mastery plays an important role in the Teaching and Learning (TnL) process and enables students to master it in the field of descriptive linguistics up to the sentence level. This study aims to examine the level of mastery in using verbs and analyze the mastery of using verbs among students. This research method uses a quantitative study design by analyzing the findings of grammar tests that have been distributed to students. Respondents involved were 100 Form Four full boarding secondary school students. The data of the study were analyzed using SPSS software assistance and analyzed using high, medium and low level determination of students marks. The data was collected from random sampling. The data was analyzed descriptively through mode score value, median score, frequency and percentage. By analyzing the findings, it indicated a level of mastery using verbs among students that can overcome the problem of using verbs. The findings revelaed that the level of mastery is at a high level. Therefore, this study shows that the level of verb mastery is potentially good and obtain a high measurement of verb mastery.